Performance Appraisal for Employee Development: Exploring Perceptions of Supervisors - Bhurtel, Anup; Adhikari, Eka Raj (International Journal of Social Sciences and Management, 2016)
The purpose of the present study was to explore the perceptions of supervisors on performance appraisal in relation to employee development adopting a qualitative design. In line with its research objective, data obtained from semi-structured interviews conducted with 14 supervisors from the proposed 10 model technical schools and the head office of the Council for Technical Education and Vocational Training (CTEVT), Nepal was analysed. The study brought forth that supervisors perceived the existing performance appraisal system less effective as it was used merely for getting employee-promotion. The supervisors were unable to appraise non-permanent employees; and even for permanent classed employees, they were obliged to keep the results confidential. They were thus unable to discuss the results with the concerned employees and jointly set goals for their further development. The study calls for establishing a comprehensive performance appraisal system for all employees in which results were analysed, and linked with plans for employee development. As the paper was confined to exploring the perception of 14 supervisors, further research could be done in future with greater number of samples. Moreover, there is room for studying the appraisees’ perception so that this issue can be explored from wider perspective aiding in the employee performance. Int. J. Soc. Sci. Manage. Vol-3, issue-2: 93-101